Bad Karma or Discrimination? Male-Female Wage Gaps among Salaried Workers in India - Ashwini Deshpande; Deepti Goel; Shantanu Khanna (Institute for the Study of Labor (IZA), 2015)
We use nationally representative data from the Employment-Unemployment Surveys in 1999-2000 and 2009-10 to explore gender wage gaps among Regular Wage/Salaried (RWS) workers in India, both at the mean, as well as along the entire wage distribution to see "what happens where". The gender log wage gap at the mean is 55 percent in 1999-2000 and 49 percent in 2009-10, but this change is not statistically significant. The Blinder-Oaxaca and the Machado-Mata-Melly decompositions indicate that, in both years, the bulk of the gender wage gap is unexplained, i.e. possibly discriminatory. They also reveal that over the decade, while the wage-earning characteristics of women improved relative to men, the discriminatory component of the gender wage gap also increased. In fact, in 2009-10, if women were 'paid like men', they would have earned more than men on account of their characteristics. In both years, we see the existence of the "sticky floor", in that gender wage gaps are higher at lower ends of the wage distribution and steadily decline thereafter. Over the ten-year period, we find that the sticky floor became stickier for RWS women. Machado-Mata-Melly decompositions reveal that, in both years, women at the lower end of the wage distribution face higher discriminatory gaps compared to women at the upper end.
Keywords: J31; J71; O53; 330; gender discrimination; wage differentials; gender; India